Controlling the tribological behavior at the friction interface by regulating the triboelectrification. (September 2021) - Luo, Ning; Feng, Yange; Zhang, Liqiang; Sun, Weixiang; Wang, Daoai; Sun, Xiaojun; Zhou, Feng; Liu, Weimin
Abstract: Friction and triboelectrification originate from the relative motion simultaneously at the interface. Charge accumulation becomes a considerable phenomenon when insulator occurs in the friction pair. A modified equipment was fabricated to explore the relationship between charge accumulation and tribological behavior in a ball-on-disc friction system. The electropositive nylon and electronegative PVC were utilized to investigate the effect of positive and negative tribocharges on the friction and wear. Loading and sliding speed were varied to probe the effect of external conditions on charge accumulation. Ionizing blower and grounding conductor were utilized to change the charge accumulation on the polymer surface. By comparing the three friction processes, the tribological behavior had a strong relationship with charge accumulation and it could be optimized by eliminating tribocharges. The friction pair showed excellent friction reduction, anti-wear performance, and good stability when there is no charge accumulation at the friction interface. Besides, the COF could be controlled by adjusting charge accumulation due to the interfacial coulombic force. This experiment not only demonstrate the closely relationship between tribology and triboelectricity, but also provided a new strategy to regulate the tribological behavior for different requirements at the interface. Graphical Abstract: The opposite tribocharges caused extra Coulombian force at the friction interface, which could increase COF and aggravate wear in the metal-polymer friction system. Charge elimination can optimize the friction stability and the wear resistance due to the strong relationship between tribological behavior and triboelectrification. Furthermore, the tribological behavior can be regulated by adjusting the potential on the polymer surface, which has promising potential to satisfy different applications in friction domain. ga1 Highlights: A friction system is fabricated to probe the relationship between tribology and triboelectrification. The charge elimination is a convenient and effective method to optimize tribological behavior. Controlling tribological behavior by regulation of tribocharges presents promising potential in practical applications.